MANAJEMEN PEMBINAAN UMAT HINDU MELALUI DHARMA DUTA DI DKI JAKARTA - Untung Suhardi (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2015)
The study is done in jakarta which in this case as the qualitative study by using qualitative analysis of the descriptive with the approach fenomenalogis.The problems a scientific writing this guidance the presence of the people who conducted ideally happened to all components life of hindus in jakarta however in practice it still looks that order to develop the struggle is still very much limited on the particular ethnic and has not embracing all of the components in managerial hindu guidance of the parishioners.The result of this research is a form of implementation dharma duta in jakarta done with the conventional one and had already commenced with modern ways applied in a surgical book, the seminar and workshop.Then in preparing dharma pracharaka own parisada in cooperation with the hindu consultan in jakarta determine a person were willing and capable of being determined based on the intensity in the conduct of direct assistance to hindus in jakarta. The implications of the implementation of dharma duta for hindus in jakarta many people with very enthusiastic welcome well the existence of dharma duta this and efforts to the figures of which there are luminance areas in jakarta to do the regeneration of a younger to a pattern of development by this may run on a sustainable basis.New paradigm in an effort to develop training of done a renewed effort to improve coordination with institution hindus other, benefit from the development of science and was technology and optimize group guide which so far has been formed.This effort was done as capital into the power of hindu in the present and future by the presence of connected of each institution that exist in jakarta either the government or private organizations. It is time now parisada city is based on the interest of all ethnic and adopt local genius that is as treasures culture in which there are values that can be actualized hindu teaching in life.